Perceptions of Non-Math Students in Learning Mathematics: Understanding the Challenges and Opportunities - Manlimos, Mercy Minguita; Patac, Louida; Patac Jr., Adriano (International Journal on Emerging Mathematics Education, 2025)
This study research on mathematics education, specifically focusing on college students who have a strong dislike for the subject. Employing a qualitative research design and an exploratory strategy, this paper analyzed narratives from 50 college students enrolled in non-mathematics courses using theme analysis. The study, conducted in a private higher education institution offering a Bachelor of Science program in Customs Administration, delved into the practical significance of mathematics in students' daily lives. The discussion section explored the paradox wherein students acknowledged mathematics' value but opted to avoid related courses. It advocated for a curriculum prioritizing practical applications of mathematical principles, emphasizing real-life scenarios to enhance student interest. The findings supported a practical approach to mathematics education to change attitudes and emphasized the significance of matching instructional tactics with students' perceived worth. The journal contributed valuable insights to mathematics education, serving as a resource for educators, researchers, and policymakers to enhance teaching methods and foster a positive learning environment for students of varying mathematical abilities.